CORE VALUE (TA’ĀWUN VALUE) IN THE DEVELOPMENT PROGRAM OF INCLUSIVE EDUCATION - Kokom Siti Komariah (Ta'dib, 2017)
Though values are fundamental aspects in education, the preliminary study shows the phenomena of ignorance of the values especially in inclusive schools. The insertion of values that support the implementation of inclusive education is much more necessary. The study aims at depicting the implementation of the main values in the development of inclusive education program at SDN Purtaco Indah Kota Bandung, as the research focus. The research used qualitative approach with descriptive analytic case study method, grounded theory, hermeneutical social, and thematic study of Al-Quran Al-Qarafi. The data were obtained through observation, interview, questionnaire, and documentary study. The results show that: 1)The foundation of the implementation of inclusive education consists of religious foundations, psychological foundations, and pedagogical foundations of ta`āwun value as a core value in inclusive education; 2) The value of ta`āwun is hierarchically elaborated into basic values, instrumental values, and practical values; 3) The implementation of the ta`āwun value, as the main value of inclusive education, includes: (a) Implementation of ta`āwun value development among teachers, teachers and parents, parents with students (ordinary and those with special need), and fellow students (ordinary and with special need); 4) The advantages of the ta`āwun value development program are: (a) Facilitating the acceptance of the students with speacial need at inclusion schools, (b) the parents become more optimistic, (c) The parents of those with special need are happy because their children can learn inclusively with normal children, (d) The majority of parents of the students with special need are able to mingle regardless of their economic background. As for the shortcomings, namely (a) The knowledge aspect for the regular students is relatively hampered because the teachers have to share the attention with the needing students who have limitations in the cognitive aspect, (b) It is very difficult to convince the parents of regular students to receive the needing students as their children’s classmates.